A educação jurídica positivista e as diretrizes do ensino jurídico: currículo e prática pedagógica no curso de direito da UFPA no horizonte das competências e habilidades - MORAES, Élcio Aláudio Silva de (Universidade Federal do Pará, 2015)
This thesis discusses the contemporary legal education from the perspective of the influence of the theoretical and methodological legacy of legal positivism on the organization of the law curriculum in Brazil. Specifically, it examines the political-pedagogical project of the UFPA law school and its curriculum, which is attached to theoretical dogmatism, clearly observed by the disciplines that follow the written law and by the unilateral pedagogy developed in class, predominantly based on lectures. The research focuses on the critical analysis of the National Curriculum Guidelines of Legal Education, which opted for critical, reflective and humanists abilities and skills, in contrast with the UFPA political-pedagogical project of its law course, organized in the traditional sense, in which persist dogmatic pedagogical practices, the teaching as transmission of knowledge, as verbalization of a content that prioritizes the formal rules and procedures, and that forgot the learning for emancipation.